Integrated flavoromics and lipidomics analysis of metabolic difference and flavor regulation mechanisms in duck subcutaneous adipose tissue - Gong, Ping; Cheng, Shengqi; Chen, Xing; Wang, Lixia; Wang, Yanan; Zhai, Mingli; Qian, Yunguo; Ye, Shengqiang; Yang, Yu (Frontiers in Nutrition, 2025)
Subcutaneous adipose tissues (SAT) are critical determinants of duck meat flavor and texture. Investigating metabolic differences in SAT deposition facilitates targeted breeding strategies for superior flavor profiles and feed formulation optimization. This study employed flavoromics and lipidomics to systematically compare the flavoromics and lipidomics profiles of SAT from Wuqin-10 duck (WQ) and Cherry valley duck (CV). Flavoromics analysis identified hexadecanal as the sole significantly upregulated differential flavor compounds in WQ ducks (P-value < 0.05), predominantly enriched in fatty acid degradation pathways. Lipidomics revealed 182 differential lipids (87 upregulated, 95 downregulated) between breeds, with Carnitine C4:1-2OH exhibiting 256-fold higher relative abundance in WQ ducks. Compositional analysis demonstrated elevated levels of long-chain triglycerides (TAGs), lysophosphatidylcholines (LPCs), and lysophosphatidylethanolamines (LPEs) in WQ ducks, whereas CV ducks showed higher abundance of phosphatidylserine (PS), phosphatidylethanolamine (PE), and phosphatidylcholine (PC). These differential lipids were significantly enriched in glycerophospholipid metabolism, GPI-anchor biosynthesis, and polyunsaturated fatty acid metabolic pathways. Integrated multi-omics analysis further identified significant positive correlations between flavor compounds (n-hexadecanoic acid and hexadecanal) and glycerolipids (TG/DG). Collectively, this work systematically elucidates substantial compositional divergences in flavor compounds and lipids between CV and WQ ducks, while flavor compound-lipid correlations reveal potential regulatory nodes within lipid metabolic networks, providing crucial molecular insights into breed-specific lipid metabolic characteristics.